2015
DOI: 10.1111/1475-4932.12195
|View full text |Cite
|
Sign up to set email alerts
|

Can Ethno‐Linguistic Diversity Explain Cross‐Country Differences in Social Capital?: A Global Perspective

Abstract: Motivated by the inconclusiveness of empirical studies on the relationship between ethno-linguistic diversity and social capital (SC) at various levels of regional aggregation, this paper provides new evidence on the relationship between the two variables at a global scale. A cross-sectional analysis of 68 developed and developing countries applying two-stage least squares estimations suggests not only that the cognitive dimension of SC (shared codes and languages) is highly important for SC formation across r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 111 publications
0
30
0
Order By: Relevance
“…In Table 3, we test the validity of the instruments employed in Michalopoulos (2012), Wang and Steiner (2015) and Churchill et al (2015). The null hypothesis of the Sargan Overidentifying restrictions test which is not overwhelmingly rejected confirms the validity of the instruments.…”
Section: Results With Tribalism As An Endogenous Variablementioning
confidence: 79%
See 2 more Smart Citations
“…In Table 3, we test the validity of the instruments employed in Michalopoulos (2012), Wang and Steiner (2015) and Churchill et al (2015). The null hypothesis of the Sargan Overidentifying restrictions test which is not overwhelmingly rejected confirms the validity of the instruments.…”
Section: Results With Tribalism As An Endogenous Variablementioning
confidence: 79%
“…Hence, we are attempting to test this hypothesis in order to isolate the effect of ethnic fragmentation within the framework of tribalism on government institutions. Wang and Steiner (2015) and Churchill et al (2015) have employed differences in elevation, land quality, and latitude as instruments for enthnolinguistic diversity. Within the framework of this study, latitude is employed which has been demonstrated by Ahlerup and Olsson (2012) to be exogenous to ethnic fragmentation and/or tribalism.…”
Section: Results With Tribalism As An Endogenous Variablementioning
confidence: 99%
See 1 more Smart Citation
“…Low hanging fruits might be found by economist exploring the working of assortation, which might improve our scant understanding of the interactions between family and business (The Economist, 2015). Homophily in human society achieves less diverse but more harmonious economies (Wang & Steiner 2015), suggesting a role for assortation hitherto overlooked in economics. Assortation, viewed in the light of the present theory might, for example, explain the ubiquity of corruption among human societies, and help biologists to better understand economic synergies found in the social phenomena they study, opening our interdisciplinary world view in a consilient way.…”
Section: Benefits Of An Extended Inclusive Fitness Theory?mentioning
confidence: 99%
“…But it is not only a neglect of the role of language in the research of social policy at the EU-level that is undermining the design of a genuine European social policy based on solidarity, it is also the rejection of the concept of linguistic diversity all together that is favoring homogeneous language communities. Wang and Steiner [7] argue that there is a relationship between linguistic fragmentation and social capital, where the latter is characterized by trust, common norms and networks. Countries with higher social capital tend to be richer.…”
mentioning
confidence: 99%